Odpowiedzi

2010-03-24T12:23:02+01:00
x²+4-(2x+1)=3x²-1-(x²+4)
x²+4-2x-1=3x²-1-x²-4
-x²-2x+8=0
Δ=4+32=36
√Δ=6
x₁=2+6 /(-2)= -4
x₂=2-6 /(-2)= 2

1)
2x+1=-7
x²+4=20
3x²-1=47

2)
2x+1=5
x²+4=8
3x²-1=11
2010-03-24T12:29:57+01:00
R= x²+4-2x-1
r= 3x²-1-x²-4

x²+4-2x-1 = 3x²-1-x²-4
-x²-2x+8=0 /(-1)
x²+2x-8 = 0
Δ= b²-4ac
Δ= 4+32=36
pierwiastek z Δ = 6

x₁= -2-6/2= -4
x₂ = -2+6/2= 2
teraz podstawiamy do 2x+1, x²+4, 3x²-1 ww. liczby i otrzymujemy
-7, 20, 47 dla x= -4
5, 8, 11 dla x=2
odp. -7, 20,47 lub 5,8,11